Palm Lipid Emulsion Droplet Crystallinity and Gastric Acid Stability in Relation to in vitro Bioaccessibility and in vivo Gastric Emptying - Hamad, Samar; Chen, Run; Zhou, Zhitong; Nasr, Pedram; Li, Ye Ling; Rafiee Tari, Niloufar; Rogers, Michael A.; Wright, Amanda J. (Frontiers in Nutrition, 2022)
It is poorly understood how the physical state of emulsified triacylglycerols (TAG) alters colloidal behavior in the gastrointestinal tract to modulate lipid digestion and absorption. We therefore aimed to investigate the individual and combined effects on fatty acid (FA) bioaccessibility using the dynamic TIM-1 in vitro digestion model and integrate the results with those from a human clinical study. Four 20% oil-in-water emulsions with overlapping particle size distributions contained either partially crystalline solid (palm stearin) or liquid (palm olein) lipid droplets at 37°C and either the colloidally acid-stable Tween 80 (2.2%) or acid-unstable Span 60 (2.5%) emulsifier. Experimental meals were fed to the TIM-1, and jejunal and ileal dialysates were analyzed over 6 hours to measure free fatty acid concentration. Cumulative FA bioaccessibility was significantly higher for the liquid stable emulsion compared to all others (P < 0.05), which did not differ (P > 0.05). Emulsified TAG physical state was associated with differences in overall bioaccessibility (higher for liquid state TAG) in the colloidally stable emulsions, but this difference was blunted in droplets susceptible to acidic flocculation. In contrast, human postprandial TAG concentrations did not differ significantly between the emulsions. The discrepancy may relate to differences in in vivo gastric emptying (GE) as were evidenced by ultrasonography. When the in vivo differences in GE were accounted for in follow-up TIM-1 experiments the findings aligned more closely. Cumulative FA bioaccessibility for the liquid stable emulsion no longer differed significantly from the other emulsions and SU’s bioaccessibility was lowest, consistent with the in vivo observations. This work highlights the potential for TAG physical state and colloidal stability to interactively alter behaviour in the gastrointestinal tract with implications for FA absorption, and the importance of establishing and improving in vitro-in vivo correlations in food-nutrition research.